The effects of grammatical gender on the processing of occupational role names in Slovene: An event-related potential study - Mikić Ljubi, Jasna; Matkovič, Andraž; Bon, Jurij; Kanjuo Mrčela, Aleksandra (Frontiers in Psychology, 2022)
The event-related potential method has proven to be a useful tool for studying the effects of gender information in language. Studies have shown that mismatch between the antecedent and the following referent triggers two ERP components, N400 and P600. In the present study, we investigated how grammatical gender affects the mental representation of the grammatical subject. A match-mismatch paradigm was used to investigate how masculine grammatical gender and gender-balanced forms (the explicit mention of masculine and feminine forms as word pairs) as role nouns affect the processing of the referent in Slovenian. The morphological complexity of Slovenian language required the use of anaphoric verbs instead of nouns/pronouns, on which previous research was based. The results showed that following both the gender-balanced and the masculine generic forms, P600 (but not N400) was observed in response to the feminine verb but not to the masculine verb. The P600 amplitude was smaller in the case of the gender-balanced form than in the case of the masculine generic form only. We have concluded that gender-balanced forms are more open to feminine continuations than masculine generic forms. This is the first ERP study in Slovenian to address the effects of processing grammatical gender, thus contributing to existing research on languages with grammatical gender. The great strength of the study is that it is one of the first ERP studies to test the mental inclusivity of gender-balanced forms.